Examination of the Satisfaction Levels of Hemodialysis Patients - Korkmaz, Murat; Yücel, Ali Serdar; ahbudak, Ercanª; Yildiz, Kaya; Yildiz, Sevilay; Karacabey, Sevcan; Dünder, Emre (Taylor and Francis Ltd., 2017)
The purpose of this study is to examine the satisfaction levels of patients who are being treated in hemodialysis unit in terms of different variables. A total of 222 patients were included in the research and they were being treated in nursing homes in the provinces of Istanbul, Sivas, Izmir, Ankara, Bolu, Gaziantep, Tekirdag and Diyarbakir. A questionnaire consisting of two parts was used as data gathering tool in the research. Reliability level of the scale items was tested and reliability coefficient (Cronbach Alpha) was found to be 0.933. It was derived from chi-square test, t-test and variance analysis techniques, frequency analysis, percentage and average values in the analysis of the acquired data. Furthermore, chi-square cross-table analysis was used in order to measure the satisfaction levels of individuals according to their demographic characteristics. At the end of the research, it was discovered that the satisfaction levels of the patients were low in general, and that dissatisfaction was on the highest level, especially in terms of information and as regards training. © 2017 Kamla Raj.
Keywords: Health Institution; Hemodialysis; Satisfaction; Scale; Treatment